2021
DOI: 10.3389/fcimb.2021.641920
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Bacterial Coinfection of a COVID-19 Patient Caused by a Genetically Adapted Pseudomonas aeruginosa Chronic Colonizer

Abstract: Pseudomonas aeruginosa is a biofilm-forming opportunistic pathogen which causes chronic infections in immunocompromised patients and leads to high mortality rate. It is identified as a common coinfecting pathogen in COVID-19 patients causing exacerbation of illness. In our hospital, P. aeruginosa is one of the top coinfecting bacteria identified among COVID-19 patients. We collected a strong biofilm-forming P. aeruginosa strain displaying small colony variant morphology from a severe COVID-19 patient. Genomic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 54 publications
3
62
0
5
Order By: Relevance
“…This is probably due to intrinsic characteristics of P. aeruginosa in terms of virulence, adaptability, and spreading features. Biofilm-forming properties of P. aeruginosa may be the cause of problematic chronic lung infections, particularly in COVID-19 patients who underwent mechanical ventilation [68]. In any case, differently from CRE and CRAB, current literature did not show a significant spread of CRPA in course of COVID-19, although it could still represent a major threat for some patients.…”
Section: Carbapenem-resistant Non-fermenting Gram-negative Bacteriamentioning
confidence: 81%
“…This is probably due to intrinsic characteristics of P. aeruginosa in terms of virulence, adaptability, and spreading features. Biofilm-forming properties of P. aeruginosa may be the cause of problematic chronic lung infections, particularly in COVID-19 patients who underwent mechanical ventilation [68]. In any case, differently from CRE and CRAB, current literature did not show a significant spread of CRPA in course of COVID-19, although it could still represent a major threat for some patients.…”
Section: Carbapenem-resistant Non-fermenting Gram-negative Bacteriamentioning
confidence: 81%
“…However, in blood isolates, we found consistently high non-susceptibility rates for the aforementioned antibiotics during both pre-pandemic and pandemic periods. P. aeruginosa has been identified as a common coinfecting pathogen in COVID-19 patients causing exacerbation of illness [ 29 , 56 , 60 , 61 , 62 ]. P. aeruginosa has shown high resistance to many antibiotics used during the COVID-period, such as carbapenems [ 48 , 63 , 64 ] and amikacin [ 48 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in opportunistic pathogens in the gut and in the airway during the course of COVID-19 also plays a significant role in worsening disease prognosis. Co-infection has been shown to be a key prognostic factor in COVID-19 [ 66 ]; for example, pulmonary aspergillosis was estimated to occur in 19–33% of COVID-19 patients [ 67 69 ], and was reported in two of the studies included in this review [ 29 , 31 ]; Pseudomonas is one of the most commonly reported pathogens isolated from COVID-19 patients with bacterial co-infection [ 70 ], which was reported in one study included in this review as well [ 37 ].…”
Section: Discussionmentioning
confidence: 99%